Baseline 18F-FDG PET/CT parameters in predicting the efficacy of immunotherapy in non-small cell lung cancer - Zheng, Lu; Bian, Yanzhu; Hu, Yujing; Tian, Congna; Zhang, Xinchao; Li, Shuheng; Yang, Xin; Qin, Yanan (Frontiers in Medicine, 2025)
ObjectiveTo analyse positron emission tomography/ computed tomography (PET/CT) imaging and clinical data from patients with non-small cell lung cancer (NSCLC), to identify characteristics of survival beneficiaries of immune checkpoint inhibitors (ICIs) treatment and to establish a survival prediction model.MethodsA retrospective analysis was conducted on PET/CT imaging and clinical parameters of 155 NSCLC patients who underwent baseline PET/CT examination at the Department of Nuclear Medicine, Hebei General Hospital. The Kaplan–Meier curve was employed to compare progression-free survival (PFS) and overall survival (OS) between the ICIs and non-ICIs group and to assess the impact of variables on PFS and OS in the ICIs group. Multivariate Cox proportional hazards regression analysis was conducted with parameters significantly associated with survival in univariate analysis.ResultsSignificant differences were observed in PFS (χ2 = 11.910, p = 0.0006) and OS (χ2 = 8.343, p = 0.0039). Independent predictors of PFS in the ICIs group included smoking history[hazard ratio (HR) = 2.522, 95% confidence interval (CI): 1.044 ~ 6.091, p = 0.0398], SUVmax of the primary lesion(HR = 0.2376, 95%CI: 0.1018 ~ 0.5548, p = 0.0009), MTVp (HR = 0.0755, 95%CI: 0.0284 ~ 0.2003, p < 0.001), and TLGp (HR = 0.1820, 95%CI: 0.0754 ~ 0.4395, p = 0.0002). These were also independent predictors of OS in the ICIs group[HR(95%CI) were 2.729 (1.125 ~ 6.619), 0.2636 (0.1143 ~ 0.6079), 0.0715 (0.0268 ~ 0.1907), 0.2102 (0.0885 ~ 0.4992), both p < 0.05)]. Age was an additional independent predictor of OS (HR = 0.4140, 95%CI: 0.1748 ~ 0.9801, p = 0.0449).ConclusionSmoking history, primary lesion SUVmax, MTVp, and TLGp were independent predictors of PFS, whilst age, smoking history, SUVmax, MTVp, and TLGp were independent predictors of OS in the ICIs group. Patients without a history of smoking and with SUVmax ≤19.2, MTVp ≤20.745cm3, TLGp ≤158.62 g, and age ≤ 60 years benefited more from ICI treatment.